Ekologi Lansekap Kawasan Taman Nasional Gunung Gede Pangrango Resot Area Bedogol - Muhammad, Wiharto (bionature, 2011)
Understanding of landscape dynamics provide profound implications on the management and landscape planning. Mount Gede Pangrango National Park  (MGPNP) has a nature which is  unique and spesific, which made this national park as one of the laboratory  for landscape ecology research. The research objectives were to observe and identified the structure, function, and dynamic of MGPNP’s landscape, particularly at Bedogol resort. The landscape’s mosaic, patch, and corridor were studied and analyzed based on ecological structure, dynamic, and function conditions, and also with various bio-physic social economic and culture which related to bioclimatic zone condition. Landscape mosaic of MGPNP was composed of various ecosystem started from spesific ecosystem of lowland tropical rain forest to the mountain forest. The identifying patch were forest, resting house, gazebo, small field, house and seedbed for protected plant and medicinal plant. The landscape corridor’s were street and pathway. There were two kind of corridor forms, which were line and hedgerow corridor.